Simulation of microbubble reconstruction using compressive holography - Syukran Hakim, Norazman; Erny Afiza, Alias; Izzati Salwani, Zaidi (Institution of Engineering and Technology, 2022)
Microbubbles (MB) are small sphere of gas enclosed in liquid. Due to their small size and unique properties, MB have been studied extensively for several application such as drug delivery, ultrasound contrast, particle tracking velocimetry, and agriculture. The main parameter for MB is the size distribution, which may varies depending on the use case. Measuring the size distribution in-situ is often difficult. The aim of this study is to develop a novel method for determining the individual size and overall size distribution of MB suspended in water. The proposed method is based on compressive holography. First, digital hologram of MB is captured using digital camera. Then, MB at multiple z-planes are reconstructed by solving an underdetermined inverse problem. The key idea is to exploit the sparsity of MB in the suspending medium and applying the compressive sensing approach to find the optimum solution. The feasibility of proposed method is demonstrated via optical simulation. Based on the simulation, the individual MB can be reconstructed and the overall size distribution has good agreement with ground truth. In conclusion, the proposed method has huge potential to be utilized for in-situ MB size measurement.